Not the righteous but sinners : M.M. Bakhtin's theory of aesthetics and the problem of reader-character interaction in Matthew's Gospel /: M.M. Bakhtin's theory of aesthetics and the problem of reader-character interaction in Matthew's Gospel. (2003) - Unknown
No abstract available